The effect of otic melanocytes destruction on the auditory and vestibular functions in vitiligo patients - Parvaneh Mahdi; Amin Amali; Mohammad Hosein Nilfroush; Masoumeh Rozbahani; Vahid Mehdizadeh Gilani; Alireza Karimi Yazdi; Samad Rezaei Khiyabanlo; Mohammad Kamali (Vesnu Publications, 2013)
Introduction: Vitiligo is a systemic disease which leads to the destruction of melanocytes of the body. The hallmark of vitiligo is the formation of white patches in the affected skin but, because of the presence of melanocytes in the auditory and vestibular apparatuses, these systems may also be involved at some point in the course of the disease. Materials and Methods: 21 patients with vitiligo (12 females, 9 males) and 21 healthy controls (11 females, 10 males) were enrolled in this case-control study. Pure tone audiometry (PTA), Auditory brainstem responses (ABR) and Vestibular evoked myogenic potential (VEMP) were carried out for all participants. Results: High frequency sensory neural hearing loss was indicated in 8 (38.09%) patients. ABR analysis revealed that 10 (47.61%) patients had an abnormal increase in latency of the wave III, which was statistically meaningful in both right and left ears (P = 0.024 and P = 0.001, respectively) and that 6 subjects (28.57%) had an abnormal prolongation of the IPL I-III. However, findings from the VEMP measurements showed no recorded responses in the left ear of 1 (4.76%) patient and statistically significant prolongations in the latency of the p13 were shown in 5 (23.80%) patients (P = 0.001). Conclusion: Because of antioxidant, ion-recycling and protective roles of melanocytes in the auditory and vestibular systems, the involvements of these systems are possible in vitiligo vulgaris. Keywords: Vitiligo vulgaris, Melanocytes, Sensoryneural hearing loss, Auditory brainstem response, Vestibular evoked myogenic potential